Knowledge, attitude and practices of pediatricians regarding malocclusion in Haryana, India - Rekha Sharma; Sushil Kumar; Anu Singla; Devender Kumar; Sonal Chowdhary (Wolters Kluwer Medknow Publications, 2016)
Introduction: Pediatricians are often the first health professional whom children visit but very few patients have presented in the orthodontic clinics with referrals from pediatricians, an indication that the primary caregivers may be deficient in the knowledge and skill to recognize cases requiring orthodontic intervention. Aim: To explore the knowledge, attitude, and practices of pediatricians regarding orthodontics. Materials and Methods: A questionnaire survey of 40 questions was conducted among pediatricians in Haryana. A cross-sectional, questionnaire-based study was conducted between January 2015 and June 2015 (6 months) among 198 pediatricians practicing in Haryana state, India. Statistical Analysis: Statistical analysis was performed using SPSS software (version 19, SPSS Inc., Chicago, IL, USA). Frequency distribution and measures of central tendency were generated for all numerical values, and descriptive and inferential analysis was done using Chi-square test. Results: Knowledge level among the study participants was low. Although a majority (84.9%) agreed for a need for oral health assessment during general examination of the children in practice less than half (41%) did so citing problems, the lack of adequate training being the most common (41%). Conclusions: The need for more education of the pediatricians regarding orthodontics was perceived. Effective and appropriate involvement of pediatric primary care clinicians can be expected only after they receive the appropriate training and encouragement and problems with the dental referral environment are addressed.